FAKTOR PENENTU AUDITOR SWITCHING SECARA VOLUNTARY STUDY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015 - 2016 - Rina Kartikasari, 14.05.52.0251; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
Abstrak This study aims to determine the effect of company size, client company growth, audit opinion, and financial distress on auditor switching. This type of research uses explanatory studies, namely research that explains the relationships between variables. The type or type of relationship in this study is the causal relationship between one or more variables. Samples were taken using purposive sampling technique. Samples totaled 107 companies from 143 manufacturing companies listed on the Indonesia Stock Exchange in 2015 and 106 companies from manufacturing companies listed on the Indonesia Stock Exchange in 2016. The hypothesis in this study was tested by logistic regression analysis method in SPSS 16 software. The study tries to test empirically the influence of client company size, client company growth, audit opinion. The results of this study indicate that the size of KAP has a significant negative effect on the switching auditor. Company size, company growth rate, audit opinion, financial distress have no effect on the auditor switching . Keywords: Auditors Switching, client company size, client company growth, audit opinion, and financial distress.